2016
DOI: 10.1016/j.ajic.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Middle East respiratory syndrome coronavirus on inanimate surfaces: A risk for health care transmission

Abstract: The Middle East Respiratory syndrome coronavirus (MERS-CoV) has been responsible for multiple health care-associated outbreaks. We investigated whether high-touch surfaces in 3 rooms of laboratory-confirmed MERS-CoV patients were contaminated with MERS-CoV RNA. We found 2 out of 51 surfaces were contaminated with MERS-CoV viral genetic material. Hence, environmental contamination may be a potential source of health care transmission and outbreaks. Meticulous environmental cleaning may be important in preventin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…SARS-CoV-2 has been demonstrated to survive on surfaces, such as plastic and steel, for up to 3 days 8 . This extensive spreading and prolonged survival opens the possibility of indirect transmission of SARS-CoV-2 from surfaces, which is consistent with data from prior coronavirus outbreaks such as Severe Acute Respiratory Syndrome (SARS) and Middle Easters Respiratory Syndrome (MERS) [9][10][11][12] . Infection clusters of SARS-CoV-2 have been reported, where no direct contact with an infected individual has occurred, but several persons in became infected 13,14 .…”
supporting
confidence: 85%
“…SARS-CoV-2 has been demonstrated to survive on surfaces, such as plastic and steel, for up to 3 days 8 . This extensive spreading and prolonged survival opens the possibility of indirect transmission of SARS-CoV-2 from surfaces, which is consistent with data from prior coronavirus outbreaks such as Severe Acute Respiratory Syndrome (SARS) and Middle Easters Respiratory Syndrome (MERS) [9][10][11][12] . Infection clusters of SARS-CoV-2 have been reported, where no direct contact with an infected individual has occurred, but several persons in became infected 13,14 .…”
supporting
confidence: 85%
“…& Human adenoviruses (HAdV) were detected from 63 of 141 (45%) fomite samples in an adult intensive care unit (ICU) in a hospital in Rio de Janeiro, Brazil, with viral loads ranging from 2.48 × 10 1 to 2.1 × 10 3 genomic copies per milliliter [69]. & Middle East respiratory syndrome coronavirus (MERS-CoV) was detected on 2 of 51 (4%) high-touch surfaces in patient rooms with laboratory-confirmed MERS-CoV patients [70].…”
Section: Presence and Abundancementioning
confidence: 99%
“…Interestingly some studies reported the presence of the virus on surfaces (patient rooms) following discharge or death, which highlights the importance of strict and proper infection control practice in healthcare facilities [11]. …”
Section: Discussionmentioning
confidence: 99%